Nursing care and implementation of care protocols for low-risk pregnant women in prepartum (Research, Society and Development, 2022)
Objective: to identify in the literature, information regarding the protocols of nursing care for low-risk pregnant women in prepartum. Method: literature review, qualitative, exploratory, with selective, analytical and interpretive reading. With the application of the inclusion criteria, 969 articles were found. After reading the titles and abstracts, 850 of them were excluded, as they did not meet the proposed theme. After a complete analysis of the remaining 119, 19 articles were selected to compose this study. Results: steps were found in the process of systematization of nursing care aiming at humanized care and autonomy in pre-delivery. Conclusion: Classifying our clinical practice, overcoming the idea of medicalized and technical nursing, are challenges that must be faced so that we can increasingly guarantee the provision of qualified health care.